Offline Teaching Practicum by ‘Online’ Generation: Indonesian Efl Pre-Service Teachers’ Voices - Atin Kurniawati (Universitas Negeri Medan, 2025)
Teaching practicum is one of the prominent issues in education faculties and many studies explored the implementation of teaching practicum in many regions by focusing on several aspects. However, after the pandemic era, how the ‘online’ generation of EFL pre-service teachers perceived their teaching practicum remains unexplored. This current study shed some light on how the ‘online’ generation of EFL pre-service teachers perceived their teaching practicum, the challenges the faced, and how ‘online’ learning during the pandemic changed their perspectives. Using narrative inquiry, the data of this study was gathered from seven graduates of English language education department who experienced online learning during the pandemic but had their teaching practicum offline. The data was collected through open-ended questionnaire and in-depth interview to elicit the story from their experiences during their enrolment in teaching practicum. The collected data were analysed thematically. The findings showed that the EFL pre-service teachers perceived positively on offline teaching practicum. Despite the challenges, they were more motivated to learn and improve their capability. Online learning during the pandemic has improved their ability in integrating technology in their teaching which boost their confidence. It also changed their belief that teaching can be flexible and adaptable to any condition. For that purposes, teachers should be creative and always improve their capability.